2016
DOI: 10.1088/1752-7155/10/4/046012
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound markers of psychological stress in skin: a pilot study

Abstract: The forehead was studied as a possible sampling site for capturing changes in volatile organic compound (VOC) profiles associated with psychological-stress. Skin-VOCs were sampled with a polydimethylsilicone (PDMS)-coupon and the resulting VOCs were recovered and analysed with two-stage thermal desorption gas chromatography-mass spectrometry.15 young adult volunteers (19 yr to 26 yr) participated in two interventions run in a randomised crossover design. One intervention, termed "Neutral", required the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…Two studies utilized different methodologies and found different stress biomarkers. The first study found changes in the concentrations of the biomarkers 2-hydroxy-1-phenylethanone, benzaldehyde, and 2-ethylhexan-1-ol in response to the stressor [53], while the second study found changes in the concentrations 1,2-ethanediol acetophenone, heptadecane, hexanedioic acid, dimethyl ester, benzyl alcohol, and benzothiazole [19]. However, in the first study, the biomarkers were found in the forehead samples, which might be produced from eccrine glands as cortisol metabolite VOCs, whereas in the second study the biomarkers were measured from apocrine glands (underarms).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies utilized different methodologies and found different stress biomarkers. The first study found changes in the concentrations of the biomarkers 2-hydroxy-1-phenylethanone, benzaldehyde, and 2-ethylhexan-1-ol in response to the stressor [53], while the second study found changes in the concentrations 1,2-ethanediol acetophenone, heptadecane, hexanedioic acid, dimethyl ester, benzyl alcohol, and benzothiazole [19]. However, in the first study, the biomarkers were found in the forehead samples, which might be produced from eccrine glands as cortisol metabolite VOCs, whereas in the second study the biomarkers were measured from apocrine glands (underarms).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, heart rate and blood pressure measurements were recorded. It was found that four stress biomarkers (benzoic acid, n-decanoic acid, a xylene isomer, and 3-carene) were present, as can be seen in Figure 4 [53]. Notably, the identified biomarkers from both studies were different.…”
Section: Volatile Organic Components (Vocs)mentioning
confidence: 93%
“…Based on the study results, combining the sampling patches with a thermal desorption unit coupled to a secondary electrospray ionization and mass spectrometry (TD-SESI-MS) setup is a promising approach for unattended automation of analysis and could be employed in non-invasive fast screening of metabolites for personalized medicine. In a pilot study [38], Martin et al investigated changes in VOC profiles for stress-related biomarkers using PDMS devices placed on the foreheads of volunteer subjects for sample collection. The effect of stress on VOCs exhaled in breath was investigated previously [39], identifying six potential marker compounds.…”
Section: Polydimethylsiloxane (Pdms)mentioning
confidence: 99%
“…In addition, PDMS films can be purchased or prepared in the laboratory using well defined protocols and can be easily shaped in any size. In addition, the thermal stability of PDMS enables the thermal desorption of extracted analytes from patches using large thermal desorption units connected to gas chromatography mass spectrometry (GC-MS) [35,36,38]. However, it is worth mentioning that before use PDMS patches require extensive cleaning and activation steps that might involve a considerable amount of preparation before sampling (4-24 h).…”
Section: Polydimethylsiloxane (Pdms)mentioning
confidence: 99%
See 1 more Smart Citation